Googling It: While News Search Results Can Affect Newsrooms’ Perception of Social Issues, Journalists Mainly Rely on It for Complementary Information - Rupar, Verica; Myllylahti, Merja; Jones, Haley-Georgia; Li, Weihua; Mohaghegh, Mahsa; Parisa, Prunella (Intellect, 2022)
This article investigates the ramifications of search engine algorithms for journalism practice and its professional commitment to serving the public interest. Taking a discipline-transcending approach that combines quantitative data analysis with an exploration of the social forces shaping knowledge production in journalism, we examine a case study involving New Zealand media’s coverage of economic recession. This inquiry addresses the question of how journalists navigate the terrain of algorithms and respond to the challenges posed by programme-based news production in relation to their professional norms. Our study highlights the significant role of search engines, particularly Google, in shaping the journalistic newsgathering process and, consequently, public understanding of social issues. The computer-assisted analysis of Google’s ‘recession’ news selection revealed distinct patterns in the distribution of news content and geographical bias towards the United States within the selection algorithm. Ethnographic research at one Auckland newsroom revealed that Google Search is a fundamental tool for journalists, albeit used primarily for basic information-gathering and fact-checking rather than in-depth investigative work.
Keywords: 1608 Sociology; 4410 Sociology; journalism; algorithms; search engines; recession; information-gathering; professional routine; public interest